2022
DOI: 10.1021/acs.nanolett.2c01744
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Probe of the Hydrogen Oxidation Reaction Intermediates on PtRu a Bimetallic Catalyst Surface by Core–Shell Nanoparticle-Enhanced Raman Spectroscopy

Abstract: In situ monitoring of the evolution of intermediates and catalysts during hydrogen oxidation reaction (HOR) processes and elucidating the reaction mechanism are crucial in catalysis and energy science. However, spectroscopic information on trace intermediates on catalyst surfaces is challenging to obtain due to the complexity of interfacial environments and lack of in situ techniques. Herein, core–shell nanoparticle-enhanced Raman spectroscopy was employed to probe alkaline HOR processes on representative PtRu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 50 publications
3
24
0
Order By: Relevance
“…Combining with XPS data and DFT calculation, we found that the different content of Ru doping tunes the catalytic activity of PtRu catalysts by regulating their electronic structure. Namely, the electronic effect also exists in the alkaline HOR mechanism [43] . The bifunctional mechanism for alkaline HOR was also observed in our Au@PtNi system [22]…”
Section: Applications Of In Situ Core‐shell Nanoparticle‐enhanced Ram...supporting
confidence: 60%
“…Combining with XPS data and DFT calculation, we found that the different content of Ru doping tunes the catalytic activity of PtRu catalysts by regulating their electronic structure. Namely, the electronic effect also exists in the alkaline HOR mechanism [43] . The bifunctional mechanism for alkaline HOR was also observed in our Au@PtNi system [22]…”
Section: Applications Of In Situ Core‐shell Nanoparticle‐enhanced Ram...supporting
confidence: 60%
“…Elsewhere, several Pt-based core-shell nanostructures having Ru, Rh, or Au as the core have shown a high performance for the HOR, however in alkaline media [15][16][17][18]. Nevertheless, the advantages of using supported metal@Pt core-shell nanostructures with a lower Pt content compared to monometallic Pt/C, yet sustaining high performance, encourages the research on those nanocatalysts for the HOR in acid media.…”
Section: Introductionmentioning
confidence: 99%
“…Despite numerous efforts devoted to activating Ni-based catalysts for alkaline HOR, there are still several issues remaining. Firstly, the feasible surface reconstruction [63] needs to be taken into consideration, as well as the validation of catalytic roles for multicomponent catalysts. The enhancement mechanism of decorations and dopants may be related to the degree of surface variation, rather than just depending on the usual electronic interaction or alloy effect.…”
Section: Summary and Perspectivementioning
confidence: 99%